KEDUDUKAN DAN FUNGSI DEWAN PERTIMBANGAN PRESIDEN DALAM SISTEM KETATANEGARAAN REPUBLIK INDONESIA MENURUT UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - Malo, Gladys Chyntia; Yohanes, Saryono; Lamataro, Cyrilius W. T (Petitum Law Journal, 2025)
This research highlights the influence and benefits of the Presidential Advisory Council (Wantimpres) in the effectiveness of presidential decision-making. In the context of political communication, effectiveness is not only determined by the speed of decisions but also by the accuracy in explaining to the public. This research focuses on three main points: (1) The position of Wantimpres in the constitutional system of the Republic of Indonesia according to the 1945 Constitution, (2) The urgency of Wantimpres in the constitutional system, and (3) The function of Wantimpres in the constitutional system according to the 1945 Constitution. The research method used is normative juridical with a literature approach. The research results show: (1) Wantimpres has limited authority with advisory powers that are recommendatory and not mandatory for the President to implement, (2) The lack of executive authority of Wantimpres reduces its effectiveness in influencing public policy, and (3) The strategic function of Wantimpres often overlaps with other institutions and lacks transparency and accountability, while its advice can be ignored without clear legal or political consequences.